Detection of Biofilm Formation among the Isolates of Staphylococcus Epidermidis by Modified Microtiter-Plate Test (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):487-92The abstract of this article is available on the PubMed website